Acupuncture treatment of hypertension with insomnia: A protocol for randomized, double-blind, placebo controlled trial research. Issue 2 (14th January 2022) - Zhu, Xun; Yan, Luda; Dou, Xuejiao; Zheng, Yanping; He, Guanglin; Liao, Meiyan; Fu, Wenbin
Abstract: Introduction: Hypertension patients often suffered from insomnia problems which lowered the quality of life. Studies have shown that acupuncture is effective to treat perimenopausal and cancer-related insomnia. However, there is a lack of randomized controlled trials to support the effectiveness of acupuncture on insomnia of hypertension patients. Methods and analysis: This study is a randomized, double-blind (patients and evaluators), and placebo-controlled clinical trial to investigate the effect of acupuncture in hypertension patients' insomnia management. We will recruit 158 hypertension patients suffering from insomnia in Bao'an People's Hospital, Shenzhen and randomly assign them into treatment group (antihypertensive drugs + acupuncture) and control group (antihypertensive drugs + sham acupuncture) in a 1:1 ratio. The patients will receive acupuncture 3 times a week for 12 weeks, and then a 6-months follow-up will be conducted after the treatment. The primary outcome is the Pittsburgh Sleep Quality Index. The secondary outcomes include sleep parameters, blood pressure dropping, sleeping pill dosage, Rating Depression Scale score, and Self-Rating Anxiety Scale score. The primary outcome will be evaluated at baseline, 4, 8, and 12 weeks, and 1, 3, and 6 months following the end of treatment. The secondary outcomes will be assessed at baseline and 12 weeks of the treatment period.